Hydrodynamic optimality of balistiform and gymnotiform locomotion. Issue 1 (4th March 2017) - Sprinkle, Brennan; Bale, Rahul; Bhalla, Amneet Pal Singh; MacIver, Malcolm A.; Patankar, Neelesh A.
Abstract: Some groups of fish have evolved to generate propulsion using undulatory elongated fins while maintaining a relatively rigid body. The fins run along the body axis and can be dorsal, ventral, dorsoventral pairs or left-right pairs. These fish are termed as median/paired fin (MPF) swimmers. The movement of these groups of fish was studied in an influential series of papers by Lighthill and Blake. In this work, we revisit this problem by performing direct numerical simulations. We interrogate two issues. First, we investigate and explain a key morphological feature, which is the diagonal fin insertion found in many MPF swimmers such as the knifefish. Not only are these results of biological relevance, but these are also useful in engineering to design bioinspired highly maneuverable underwater vehicles. Second, we investigate whether there is a mechanical advantage in the form of reduced cost of transport (COT) (energy spent per unit distance traveled) for not undulating the entire body. We find that a rigid body attached to an undulating fin leads to a reduced COT.